Exploring the effect of novel N-butyl-6-methylquinolinium bis(trifluoromethylsulfonyl)imide ionic liquid addition to poly(methyl methacrylate-co-methacrylic) acid electrolyte system as employed in gel-state dye sensitized solar cells - Sundararajan, V. (Elsevier Ltd, 2017)
With the aim of replacing liquid electrolytes in dye sensitized solar cells (DSSCs) due to the evident issues the system has, we have prepared and optimized gel polymer electrolytes (GPEs) consisting of poly(methyl methacrylate-co-methacrylic) acid, P(MMA-co-MAA), sodium iodide (NaI), iodine (I2), ethylene carbonate (EC), propylene carbonate (PC) with a novel lab-made ionic liquid N-butyl-6-methylquinolinium bis(trifluoromethylsulfonyl)imide C4mquinNTf2. Synthesized via metathesis following an alkylation, the quinolinium based ionic liquid has a yield of 87%. The highest ionic conductivity obtained for this system is 2.26 × 10−3 S cm−1 at room temperature for the GPE at 25 wt.% of C4mquinNTf2. XRD and FTIR studies have been done to confirm the formation of complexes of the materials. With a standard DSSC arrangement of glass/FTO/TiO2/N719dye/electrolyte/Pt/FTO/glass, the co-polymer based conducting electrolyte displayed power conversion efficiency of 5.67% with a maximum short circuit current density (Jsc) of 15.32 mA cm−2, open circuit voltage (Voc) of 0.62 V and fill factor of 59% at 25 wt.% of C4mquinNTf2 under AM 1.5 (100 mW cm−2) illumination. The Nyquist plot and Bode plot studies have been done in order to understand the electrochemical properties of the GPE based DSSCs. © 2017 Elsevier Ltd